(untitled) (Medico Legal Update, 2020)
Background and Objective: It is important to know the trends, nature, sevesrity and outcome of acute poisoning cases in order to take up appropriate planning, time lapse, first aid and recovery. This study is to assess the trends and outcome of acute poisoning cases in a tertiary care hospital in Khammam. Materials and Methods: This is a retrospective study conducted in a tertiary care hospital attached to a medical institution in Khammam. The study includes 126 cases and data regarding age, sex, time elapsed after intake, circumstances of poisoning, name of the poisonous substance, chemical type, duration of hospitalization, severity and outcome collected in the Proforma. Results: Incidence was common among 21-30 yr. old married Hindu male laborers from rural background belonging low socioeconomic classes with only primary education. Majority of the incidents occurred in the victim’s home during the day time. Maximum number of cases were encountered during the Rainy season and in the month of November. Organophosphorus insecticides and poisoning by snake bite were the commonest types of poisoning. Majority of the acute poisoning cases were hospitalized within one hour of toxic exposure. Maximum number of patients stayed in hospital for up to 7 days and recovered. Family problems and financial problems were the most common reasons behind poisoning. Overall mortality was found to be 3.05% and 38 cases succumbed to the poisoning. Conclusion: Poisoning was common in young males. Maximum number of cases encountered in Rainy season. Organophosphorus insecticides and poisoning by snake bite were the commonest types of poisoning. Majority of the acute poisoning cases were hospitalized within one hour of toxic exposure. The overall mortality was substantially high, mainly contributed by self-poisoning with insecticides. Early care in a tertiary care center may help to reduce mortality in India.